Investigations into living systems, artificial life, and real-world solutions - Magoulas, George D.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book provides original research on the theoretical and applied aspects of artificial life, as well as addresses scientific, psychological, and social issues of synthetic life-like behavior and abilities"--Provided by publisher.
Resistance of cell in fractal growth in electrodeposition -- Propagation of front waves in myelinated nerve fibres: new electrical transmission lines constituted of linear and nonlinear portions -- What does artificial life tell us about death? -- A Constructive approach to the evolution of the planning ability -- Noise power spectrum for firecrackers -- Traffic noise: 1/f characteristics -- Existence of positive solutions for generalized p-Laplacian BVPs -- Mathematical model to assess the relative effectiveness of Rift Valley Fever countermeasures -- Resource distribution strategies for mitigation of cross-regional influenza pandemics -- A computational model of mitigating disease spread in spatial networks -- Simulating the spread of an epidemic in a small rural Kansas town -- A structural model to investigate factors affect patient satisfaction and revisit intention in Jordanian hospitals -- Generating fully bounded chaotic attractors -- Orbit of an image under iterated System II -- Superior Koch curve -- Mitigation strategies for foot and mouth disease: a learning-based approach -- Considerations on strategies to improve EOG signal analysis -- An autonomous multi-agent simulation model for acute inflammatory response -- Rough set based clustering using active learning approach -- Intuitionistic fuzzy 2-metric space and some topological properties -- Folding theory for fantastic filters in BL-algebras -- An observer approach for deterministic learning using patchy neural networks with applications to fuzzy cognitive networks.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed April 17, 2013).
Keywords: Biological systems -- Simulation methods; Artificial life -- Mathematics; Neural networks (Computer science); Social sciences -- Mathematics; Artificial intelligence; Cognitive networks; Computational linguistics; Intelligent planning; Machine learning; Neural networks; Electronic books